Characterization of regulatory T cells in obese omental adipose tissue in humans. Issue 2 (8th January 2019) - Wu, Dan; Han, Jonathan M.; Yu, Xin; Lam, Avery J.; Hoeppli, Romy E.; Pesenacker, Anne M.; Huang, Qing; Chen, Virginia; Speake, Cate; Yorke, Ekua; Nguyen, Nam; Sampath, Sharadh; et al.
Abstract: Obesity‐associated visceral adipose tissue (AT) inflammation promotes insulin resistance and type 2 diabetes (T2D). In mice, lean visceral AT is populated with anti‐inflammatory cells, notably regulatory T cells (Tregs) expressing the IL‐33 receptor ST2. Conversely, obese AT contains fewer Tregs and more proinflammatory cells. In humans, however, there is limited evidence for a similar pattern of obesity‐associated immunomodulation. We used flow cytometry and mRNA quantification to characterize human omental AT in 29 obese subjects, 18 of whom had T2D. Patients with T2D had increased proportions of inflammatory cells, including M1 macrophages, with positive correlations to body mass index. In contrast, Treg frequencies negatively correlated to body mass index but were comparable between T2D and non‐T2D individuals. Compared to human thymic Tregs, omental AT Tregs expressed similar levels of FOXP3, CD25, IKZF2, and CTLA4, but higher levels of PPARG, CCR4, PRDM1, and CXCL2 . ST2, however, was not detectable on omental AT Tregs from lean or obese subjects. This is the first comprehensive investigation into how omental AT immunity changes with obesity and T2D in humans, revealing important similarities and differences to paradigms in mice. These data increase our understanding of how pathways of immune regulation could be targeted to ameliorate AT inflammation in humans. Abstract : The proportion of regulatory T cells (Tregs) in human omental adipose tissue decreases in obesity. These human omental adipose Tregs exhibit a tissue‐specific phenotype but lack ST2 expression, in contrast to Tregs resident in mouse epididymal adipose tissue.